HTRA1-Related Cerebral Small Vessel Disease: A Review of the Literature - Uemura, Masahiro; Nozaki, Hiroaki; Kato, Taisuke; Koyama, Akihide; Sakai, Naoko; Ando, Shoichiro; Kanazawa, Masato; Hishikawa, Nozomi; Nishimoto, Yoshinori; Polavarapu, Kiran; Nalini, Atchayaram; Hanazono, Akira; et al. (Frontiers in Neurology, 2020)
Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) is clinically characterized by early-onset dementia, stroke, spondylosis deformans, and alopecia. In CARASIL cases, brain magnetic resonance imaging (MRI) reveals severe white matter hyperintensitites (WMHs), lacunar infarctions, and microbleeds. CARASIL is caused by a homozygous mutation in high-temperature requirement A serine peptidase 1 (HTRA1). Recently, it was reported that several heterozygous mutations in HTRA1 also cause cerebral small vessel disease (CSVD). Although patients with heterozygous HTRA1-related CSVD (symptomatic carriers) are reported to have a milder form of CARASIL, little is known about the clinical and genetic differences between the two diseases. Given this gap in the literature, we collected clinical information on HTRA1-related CSVD from a review of the literature to help clarify the differences between symptomatic carriers and CARASIL and the features of both diseases. Forty-six symptomatic carriers and twenty-eight patients with CARASIL were investigated. Twenty-eight mutations in symptomatic carriers and twenty-two mutations in CARASIL were identified. Missense mutations in symptomatic carriers are more frequently identified in the linker or loop 3 (L3)/loop D (LD) domains, which are critical sites in activating protease activity. The age at onset of neurological symptoms/signs were significantly higher in symptomatic carriers than in CARASIL and the frequency of characteristic extra-neurological findings and confluent WMHs were significantly higher in CARASIL than in symptomatic carriers. As previously reported, heterozygous HTRA1-related CSVD has a milder clinical presentation of CARASIL. It seems that haploinsufficiency can cause CSVD among symptomatic carriers according to the several patients with heterozygous nonsense/frameshift mutations. However, the differing locations of mutations found in the two diseases indicates that distinct molecular mechanisms influence the development of CSVD in patients with HTRA1-related CSVD. These findings further support continued careful examination of the pathogenicity of mutations located outside the linker or LD/L3 domain in symptomatic carriers.